Dietary Intake of Calcium and Magnesium in Relation to Severe Headache or Migraine - Meng, Shu-Han; Wang, Ming-Xue; Kang, Li-Xin; Fu, Jin-Ming; Zhou, Hai-Bo; Li, Xin; Li, Xia; Li, Xue-Ting; Zhao, Ya-Shuang (Frontiers in Nutrition, 2021)
Background: Migraine is a common neurological disorder and is affected by nutrients. Calcium and magnesium are essential minerals that play an important role in nerve function. So we investigated the relationship between dietary calcium and magnesium and migraine. Methods: We extracted 10798 adults from the National Health and Nutrition Examination Surveys (NHANES) of America in 1999 to 2004. We classified patients who reported having severe headache or migraine as having possible migraine. Multivariable logistic regression and restricted cubic spline regression were conducted to determine the association between dietary calcium and magnesium and migraine. Results: We found that the adjusted ORs of the association between dietary calcium and magnesium and migraine for comparing the highest quintile intake with the lowest quintile intake were 0.76 (95% CI: 0.63-0.93, P = 0.007) and 0.69 (95% CI: 0.55-0.86, P = 0.001), respectively. For women, the adjusted ORs of dietary calcium and magnesium were 0.71 (95% CI: 0.56-0.91, P = 0.007) and 0.63 (95% CI: 0.47-0.83, P = 0.001), respectively. For men, the adjusted OR was 0.69 (95% CI: 0.50-0.94, P = 0.018) comparing the highest and the lowest quintile of calcium intake, but there was no statistically significant relationship between dietary magnesium intake and migraine. Joint analyses showed that the OR in the high-calcium and high-magnesium group was 0.74 (95% CI: 0.60-0.92, P = 0.006) compared with the low-calcium and low-magnesium group in women. Conclusions: High dietary intake of calcium and magnesium, independently or in combination, were inversely associated with migraine in women. For men, high dietary calcium was negatively related to migraine, but magnesium was not associated with migraine.